A Novel Loss Minimization Algorithm for the 3-Port Converter in a Multi-Subgrid Microgrid - Rajarshi Basu; Mahesh Kumar Mishra (IEEE Access)
The integration of distributed energy resources and decentralized power generation through microgrids has transformed modern power systems. To support this transition, various multiport converter topologies with reduced components have been introduced. Among them, the 3-port converter, previously proposed by the authors, optimizes the integration of different microgrid entities while minimizing the switch count. However, this design increases current flow in certain devices, leading to higher system losses. To address this issue, this paper presents a novel loss minimization algorithm for the 3-port converter. A comprehensive power loss model is developed, accounting for both conduction and switching losses, which is used to develop the objective function. The algorithm employs an optimization function, “fmincon”, that uses a trust region method based on the interior point technique to minimize the objective function. To enhance computational efficiency, a graphical analysis is integrated into the algorithm to predefine solutions for specific scenarios and select optimal input parameters. Next, a port current angle adjustment strategy is introduced to embed the optimization results into the microgrid control structure, ensuring efficient converter operation. The algorithm is validated through Controller Hardware-in-the-Loop (C-HIL) experimentation on a multi-subgrid microgrid setup using the OPAL-RT OP4510 simulator. The algorithm achieves an average reduction of 32 to 46% in losses compared to the worst-case scenario, depending on power flow conditions, demonstrating significant improvements in system efficiency. Additionally, it outperforms other optimization methods in computational speed, confirming its effectiveness in real-time applications.